2005
DOI: 10.1213/01.ane.0000146959.71250.86
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Inhaled Halothane, Isoflurane, and Sevoflurane During Acute Normovolemic Hemodilution in Dogs

Abstract: The hemodynamic response to acute normovolemic hemodilution (ANH) can be affected by the anesthetics used. We randomized 18 mongrel dogs to undergo ANH with 3 different inhaled anesthetics: halothane, isoflurane, or sevoflurane. Hemodynamics, oxygen transport, and gastric pH were measured before blood withdrawal, at the end of hemodilution, and 30 and 60 min after the end of hemodilution. The baseline measurements of all hemodynamic variables were similar among groups, with the exception of heart rate, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
1
7
0
7
Order By: Relevance
“…2 Compensatory mechanisms of ANH have been well studied, including the influence of depth and type of anaesthesia on haemodynamic response to haemodilution. 3 However, studies on the critical limits of lower haemoglobin under haemodilution on the structure and function of different organs are scarce. Because of an increase in stroke volume to compensate acute anaemia, cardiac tolerance to ANH has been the focus of clinical and experimental investigations.…”
mentioning
confidence: 99%
“…2 Compensatory mechanisms of ANH have been well studied, including the influence of depth and type of anaesthesia on haemodynamic response to haemodilution. 3 However, studies on the critical limits of lower haemoglobin under haemodilution on the structure and function of different organs are scarce. Because of an increase in stroke volume to compensate acute anaemia, cardiac tolerance to ANH has been the focus of clinical and experimental investigations.…”
mentioning
confidence: 99%
“…73 In some recent experimental studies, acute normovolemic hemodilution was well tolerated, which corroborates tolerance to anemia. [74][75][76] Fantoni DT et al 74 showed in a study with 18 dogs that the hemodynamic response to acute normovolemic hemodilution was characterized by improvement of the cardiac index, independent of the evaluated anesthetic agent. Otsuki DA et al 75 published an experimental study with pigs submitted to normovolemic hemodilution.…”
Section: Transfusion In Heart Diseasementioning
confidence: 99%
“…Essa manutenção da estabilidade hemodinâmica é reflexo da manutenção de um estado de normovolemia, apesar da hemorragia, e a decisão de evitar o uso de hemocomponentes eritrocitários foi baseada em estudos anteriores de hemodiluição normovolêmica aguda (HNA) (Van der Linden et al, 1998;Fantoni et al, 2005;Jamnicki et al, 2003). Entretanto, deve-se ressaltar que esta abordagem restritiva só foi possível mediante controle rígido dos parâmetros vitais e de equipe treinada na técnica de HNA, mantendo uma hemodiluição normovolêmica permissiva, e manutenção de uma bolsa previamente testada e reservada caso houvesse desestabilização clínica (Madjdpour e Spahn, 2005;Madjdpour et al, 2006).…”
unclassified